Belanja Pemerintah menurut Fungsi dan Pertumbuhan Ekonomi di Maluku Utara: Analisis Tabel I-O dan Regresi Data Panel - Zaidan Najmuddin; Amalia Rizkiyani (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
The government has a contribution to ensuring the stability of economic growth. The existence of regional autonomy and fiscal decentralization gives the authority to develop their regions independently by utilizing their potential. In 2020, Maluku Utara's economic growth grew by 4.92 percent, the value tends to be stable, but the contribution to the national economy is very slight. From a fiscal perspective, a component that determines the economic direction is government spending. However, Maluku Utara's government spending tends to be weak and fluctuating. The condition indicates that the relationship between government spending and economic growth is inconsistent. Several objectives were set to provide an overview of the economic structure, analyze the impact of government spending on the output and value-added of the economic sector, and identify government spending by the function that affects economic growth in Maluku Utara. This study uses the I-O table impact analysis and panel data regression analysis. Based on the impact analysis of the I-O table, capital spending has the most output impact and added value in the construction sector. Meanwhile, government consumption and total government spending impact the Government Administration sectors most. Then, from the panel data regression analysis results, three variables have a significant influence, namely spending by function on economics, education, and health. However, there is an anomaly in the government spending on the economy with a negative effect of 0.003190. That indicates the items allocated to government spending by function on economics in Maluku Utara are ineffective.